Critical Role of IP-10 on Reducing Experimental Corneal Neovascularization. (September 2015) - Liu, Gaoqin; Zhang, Wenpeng; Xiao, Yanhui; Lu, Peirong
Abstract Aim and scope: To address the role of interferon-induced protein of 10 kDa (IP-10) in the course of corneal neovascularization (CrNV) in a mouse model of experimental corneal neovascularization. Material and method: BALB/c mice that were 7- to 8-week-old male were included in the study. Corneal injury was induced by NaOH. Mice were randomly divided into 2 groups of IP-10 and vehicle. The alkali-treated eyes received 5 μl of 5 μg/ml IP-10 dissolved in 0.2% sodium hyaluronate for IP-10-treated group, or 5 μl of 0.2% sodium hyaluronate for vehicle-treated group twice a day for 7 days immediately after the alkali injury. 2 weeks after alkali injury, corneas were removed and used for whole mount CD31 staining. The percentages of neovascularization on corneal photographs were examined with digital image analysis. In other experiments, at indicated time intervals, the corneas were removed. Angiogenic factor expression in the early phase after injury was quantified by real-time PCR and western blot. The VEGF expression in macrophages infiltrating into burned corneas was examined by Flow cytometry (FCM) and immunofluorescence. Tube formation and cell proliferation of human retinal endothelial cells (HRECs) were detected after being stimulated with IP-10 in vitro. Results: The mRNA and protein expression of IP-10 and C-X-C motif chemokine receptor 3 (CXCR3) was augmented after the alkali injury (p < 0.05). Compared with vehicle-treated mice, IP-10-treated mice exhibited reduced CrNV 2 weeks after injury, as evidenced by diminished CD31-positive areas (p < 0.05). Concomitantly, the intracorneal mRNA and protein expression enhancement of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) was lower in IP-10-treated mice than in vehicle-treated mice after injury (p < 0.05). Moreover, IP-10 inhibited HREC tube formation and proliferation in vitro. Conclusion: IP-10-treated mice exhibited reduced alkali-induced CrNV through decreasing intracorneal VEGF and bFGF expression, and inhibiting endothelial cell proliferation and tube formation.